Effects of Tai Chi and cognitive behavioral therapy for insomnia on improving sleep in older adults: Study protocol for a non-inferiority trial - Danny J. Yu; Angus P. Yu; Shirley X. Li; Rachel N.Y. Chan; Daniel Y. Fong; Derwin K.C. Chan; Stanley S. Hui; Ka Fai Chung; Jean Woo; Chenchen Wang; Michael R. Irwin; Parco M. Siu (Elsevier, 2023)
Background/Objective: Insomnia is a prevailing health problem among older adults. Tai Chi, a popular mind-body exercise practiced by older people in various oriental communities, has been shown to improve sleep. However, Tai Chi has not been directly compared to cognitive behavioral therapy for insomnia (CBT-I), which is the first-line non-pharmacological treatment for insomnia in older adults. This study aims to examine whether Tai Chi is non-inferior to CBT-I as a treatment for insomnia in older adults. Methods: This is a single-center, assessor-blinded, non-inferiority randomized controlled trial comparing Tai Chi and CBT-I in 180 older adults aged ≥50 years with chronic insomnia according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. Participants will be randomly assigned to either the Tai Chi or CBT-I group. Interventions will last for 3 months with a 12-month follow-up. The primary outcome is self-perceived insomnia severity measured by Insomnia Severity Index (ISI) at 3 months and at 15 months. The secondary outcomes include the remission rate of chronic insomnia, insomnia treatment response, subjective sleep quantity and quality, 7-day actigraphy, 7-day sleep diary, sleep medication, health-related quality of life, mental health, body balance and lower extremity function, adverse events, habitual physical activity, and dietary intake. Measurements will be conducted at baseline, 3 months, and 15 months by outcome assessors who are blinded to the group allocation. Discussion: This will be the first non-inferiority randomized controlled trial to compare the efficacy and long-term outcomes of Tai Chi versus CBT-I for treating insomnia in older adults. This study will be of clinical importance as it supports the use of Tai Chi as an alternative non-pharmacological approach for insomnia treatment and sustainable management.